2012
DOI: 10.3141/2311-16
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Algorithm for Resolution of Conflicting Transit Signal Priority Requests

Abstract: The goal of this study was the development and evaluation of an algorithm for resolving conflicting requests for transit signal priority (TSP). This algorithm was designed to work with actual traffic controllers without the need for new hardware or software installations. The algorithm was tested in VISSIM microsimulation and ASC/3 software-in-the-loop controllers on an intersection that will be upgraded to serve two conflicting bus rapid transit (BRT) lines. The ASC/3 logic processor was used to control built… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Rule-based, mainly reactive priority logic is even embedded or custom developed (see e.g. [58,59]) into the new-generation signal controllers. It is also offered as complementary element of the well-known signal control strategies split cycle offset optimisation technique (SCOOT), Sydney coordinated adaptive traffic system (SCATS), realtime advanced priority and information delivery (RAPID), balancing adaptive network control method (BALANCE), microprocessor optimised vehicle actuation (MOVA), and traffic-responsive urban control (TUC): † SCOOT [60,61] grants priority according to a schedule-adherence condition, mainly via green extensions and stage recalls; recent versions allow also for stage skipping.…”
Section: Real-time Strategiesmentioning
confidence: 99%
“…Rule-based, mainly reactive priority logic is even embedded or custom developed (see e.g. [58,59]) into the new-generation signal controllers. It is also offered as complementary element of the well-known signal control strategies split cycle offset optimisation technique (SCOOT), Sydney coordinated adaptive traffic system (SCATS), realtime advanced priority and information delivery (RAPID), balancing adaptive network control method (BALANCE), microprocessor optimised vehicle actuation (MOVA), and traffic-responsive urban control (TUC): † SCOOT [60,61] grants priority according to a schedule-adherence condition, mainly via green extensions and stage recalls; recent versions allow also for stage skipping.…”
Section: Real-time Strategiesmentioning
confidence: 99%
“…Kim et al (2012) proposed a priority-based rule that considered the total headway delay of buses applying for the same priority, and the processor selected the TSP action with the largest headway delay. Zlatkovic et al (2012) designed a rule-based algorithm to classify conflicting TSP calls on a case-by-case basis during each cycle in accordance with the current intersection operation.…”
Section: Introductionmentioning
confidence: 99%
“…(Zlatkovic et al, 2012b, Zlatkovic et al, 2012a, Zlatkovic et al, 2013, (Stevanovic et al, 2011), (Kim and Rilett, 2005)). This is mainly due to the sensitivity of TSP efficiency to several parameters such as intersection layout, vehicular flow rates, bus headway, bus stop locations, and signal coordination (Ngan et al, 2004).…”
Section: Microsimulation Methods To Evaluate the Effect Of Tspmentioning
confidence: 99%
“…In these strategies, the first bus that requests priority will be granted and all the other requests will be ignored until the system is restored to its normal condition. Head et al (2006) and Zlatkovic et al (2012a) showed that this method is not an efficient TSP strategy and even may occasionally perform worse than a Non-TSP strategy. Head et al (2006) presented a decision model for bus priority handling of traffic signals.…”
Section: Conflicting Prioritiesmentioning
confidence: 99%
See 1 more Smart Citation